Activated P2X receptors can up-regulate the expressions of inflammation-related genes via NF-κB pathway in spotted sea bass (Lateolabrax maculatus) - Sun, Zhaosheng; Gao, Qian; Wei, Youchuan; Zhou, Zhigang; Chen, Yuxi; Xu, Chong; Gao, Jiaqi; Liu, Danjie (Frontiers in Immunology, 2023)
P2X receptors, including seven subtypes, i.e., P2X1-7, are the ligand-gated ion channels activated by the extracellular ATP playing the critical roles in inflammation and immune response. Even though the immune functions of P2X receptors have been characterized extensively in mammals, their functions in fish remain largely unknown. In this study, four P2X receptor homologues were characterized in spotted sea bass (Lateolabrax maculatus), which were named LmP2X2, LmP2X4, LmP2X5, and LmP2X7. Their tissue distributions and expression patterns were then investigated by real-time quantitative PCR (qPCR). Furthermore, their functions in regulating the expressions of inflammation-associated genes and possible signaling pathway were examined by qPCR and luciferase assay. The results showed that they share similar topological structures, conserved genomic organization, and gene synteny with their counterparts in other species previously investigated. And the four P2X receptors were expressed constitutively in the tested tissues. In addition, the expression of each of the four receptor genes was significantly induced by stimulation of Edwardsiella tarda and/or pathogen-associated molecular patterns (PAMPs) in vivo. Also, in primary head kidney leukocytes of spotted sea bass, LmP2X2 and LmP2X5 were induced by using PAMPs and/or ATP. Notably, the expressions of CCL2, IL-8, and TNF-α recognized as the pro-inflammatory cytokines, and of the four apoptosis-related genes, i.e., caspase3, caspase6, caspase7, and P53, were differentially upregulated in the HEK 293T cells with over-expressed LmP2X2 and/or LmP2X7 following ATP stimulation. Also, the over-expression of LmP2X4 can upregulate the expressions of IL-8, caspase6, caspase7, and P53, and LmP2X5 upregulates of IL-8, TNF-α, caspase7, and P53. Then in the present study it was demonstrated that the activation of any one of the four receptors significantly upregulated the activity of NF-κB promoter, suggesting that the activated LmP2Xs may regulate the expressions of pro-inflammatory cytokines via the NF-κB pathway. Taken together, the four P2X receptors were identified firstly from fish species in Perciformes, and they participate in innate immune response of spotted sea bass possibly by regulating the expressions of the inflammation-related genes. Our study provides the new evidences for the P2X receptors’ involvement in fish immunity.